AL-GHAZALI DAN PEMIKIRANNYA TENTANG PENDIDIKAN TASAWUF - Saputra, Tomi; Wahid, Annisa (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2023)
This research aims to uncover Al-Ghazali's thoughts on Sufism and unveil and to highlight Al-Ghazali's role in the development of Sufism as an academic discipline and spiritual movement within the Islamic world. The methodology employed in this study involves literature review and analysis of Al-Ghazali's works, particularly his seminal work